Primary extragastrointestinal stromal tumors of the prostate: A case report and literature review - Yang, Yuxuan; Sun, Dengshun; Tang, Kun (Frontiers in Oncology, 2022)
Gastrointestinal stromal tumors (GISTs) are the main stromal tumors of the digestive tract. Extragastrointestinal stromal tumors (EGISTs) typically originate outside the gastrointestinal tract; are not associated with the stomach or intestinal walls; and are mainly derived from the mesentery, peritoneum, posterior peritoneum, bladder, and scrotum. However, EGISTs from the prostate are rare. Here, we present a case of EGIST that passed off in the prostate of a 62-year-old man. The patient undergoes transrectal guided trans-perineal prostate puncture, and pathological reports suggest a GIST. Tumor cells are spindle-shaped, and no obvious neoplastic necrosis is seen in the sections. Immunohistochemical results are robustly positive for CD117, DOG-1, and CD34 expression. The patient had a good prognosis after treatment with imatinib, no recurrence and no metastases after six months of follow-up, and the prognosis was good. This article also provides a literature review and discussion of the treatment of EGISTs.